The Counseling on COVID-19 Health Protocol Discipline in Sei Jangkit Village, Bataguh District, Kapuas Regency - Irfan Zamzani (UMBanjarmasin, 2021)
The spread of COVID-19 cases that continue to appear, especially in Central Kalimantan Province, is a major concern in an effort to help the community to be free from this virus. The continuous transmission of COVID-19 cases is caused by the unfavorable behavior of the community towards the prevention program that has been instructed by the Government. Based on these problems, it is necessary to disseminate information on the discipline of COVID-19 health protocols. This activity was carried out in Sei Jangkit Village, Bataguh District, Kapuas Regency, Central Kalimantan Province. This activity aims to raise awareness of the people and to improve healthy lifestyle, also to prepare themselves in new adaptations to prevent the transmission of COVID-19. There are five stages in this activity including socialization, data collection of knowledge before counseling, counseling, distribution of leaflets, and data collection of knowledge after counseling. The results achieved from this service activity are, firstly, public insight and knowledge about the COVID-19 health protocol discipline is increased, secondly the community has a high awareness of the dangers of COVID-19, thirdly the awareness to remind each other and invite other people to protect themselves from COVID-19 is raised